Analisis Tingkat Utilisasi Gudang (Studi Kasus di Gudang Perum Bulog) - Alhori Alhori; Machfud Machfud; Rokhani Hasbullah (Universitas Tidar, 2020)
Warehouse provides a large share to support the performance of a company engaged in logistics. Perum Bulog is Indonesia state-own enterprise whose has a national network and warehouse units in almost all regions in Indonesia from Aceh to Papua. The purpose of this study was to analyze the warehouse utilization rates, the potential benefits of warehouse rentals, and the level of the difference of warehouse utilization in surplus and deficit areas. The results showed that from four regional division sampling found that the largest utilization is in the North Sumatra area at 68.81%. Other regional division utilizations are West Java (57.68%), South Sulawesi (30.46%), and West Kalimantan (43.83%). There is a difference level of utilization between the surplus warehouse area and the deficit area, which indicates a difference in the supply and demand patterns. The calculation between the surplus group and the deficit group done to determine the gap magnitude that occur within the two groups. The potential benefits from the warehouse rentals produce when the warehouse experiences a low utilization rate are 4.757 billion Rupiah.